PREVALENCE OF NEUROPATHIC PAIN IN LOW BACK PAIN PATIENTS AT COMMUNITY HEALTH CENTER - M, Muna; Pambudi, Pagan (Journal of Pain, Headache and Vertigo, 2025)
Low back pain (LBP) is a musculoskeletal disorder that is widely found in the community starting at the age of 25 years and increasing at 50 years. Patients who experience LBP mostly experience neuropathic pain as much as 37% which complicates management. The neuropathic pain component is rarely considered in First Level Health Facilities (FKTP) due to lack of knowledge about simple clinical instruments that can identify pain characteristics and lack of data or research on neuropathic pain in LBP in FKTP so that the management of neuropathic pain in LBP in FKTP is less comprehensive. Therefore, research on neuropathic pain in LBP patients in primary care facilities needs to be done. This research aim to determine the prevalence of neuropathic pain among LBP patients at Puskesmas Simpang Empat 2 Banjar Regency. The study approach used was descriptive, using variables such as Low Back Pain (LBP), age, and gender. This research included LBP patients from Puskesmas Simpang Empat. 2.The research employed Pain Detection Questionnaire (PD-Q). The sample method used was incidental sampling. The results shows that During the study period, 95 samples were collected, with LBP patients with neuropathic pain accounting for 42 (44.2%), nociceptive 32 (33.7%), and ambiguous 21 (22.1%). According to gender, 58.9% were women and 41.1% were men. The greatest age group (40-49 years) had a frequency of 27.4%, while the lowest frequency (<20 years) was only 1.1%. Neuropathic pain is a prevalent issue in clinical practice.